Correction to: Introducing multiple-choice questions to promote learning for medical students: effect on exam performance in obstetrics and gynecology (Archives of Gynecology and Obstetrics, (2020), 302, 6, (1401-1406), 10.1007/s00404-020-05758-1) - Jud, Sebastian; Cupisti, Susanne; Frobenius, Wolfgang; Winkler, Andrea; Schultheis, Franziska; Antoniadis, Sophia; Beckmann, Matthias; Heindl, Felix (Archives of Gynecology and Obstetrics, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s00404-021-06112-9.
CRIS-Team Scopus Importer:2021-07-02